Extent of Utilization, Perceived Advantages and Disadvantages and Effect on Teacher Productivity of Generative AI Tools - Jake M Laguador (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: Generative AI is now reshaping either positively or negatively the nature of instructional and administrative work of teachers which makes its effect on productivity an important matter for consideration. This study explores on the utilization, perceived pros and cons and the effects on teacher productivity of Gen AI tools. Methodology: Quantitative descriptive type of research was utilized in the study involving 101 Filipino teachers teaching in the primary and secondary levels with major fields of specialization in Science, Math, English and Technology and Livelihood Education. A survey questionnaire using Google Form was used to collect data for one month with focus group discussion for validation of the results. Main Findings: Result showed that ChatGPT, Grammarly and Quillbot are the most commonly used Gen AI tools by teachers. The use of Gen AI tools has positive effect on productivity in terms of preparing lessons, content materials, strategies and assessments which describes their intention to continue utilizing it towards achieving certain level of productivity regardless of sex and field of specialization. Teachers who expressed high level of Gen AI utilization are also those who perceived high advantages and observed higher effect on productivity. Novelty/Originality of this study: The study provides an empirical evidence and multi-dimensional analysis on utilization of Generative AI tools among teachers who are considered developing users that will be used by educational managers to inform policy development, capacity-building programs, and strategic decision-making for the effective, ethical and responsible integration of Generative AI tools to enhance teacher productivity and instructional quality.